Modal Sosial Masyarakat dalam Konservasi Daerah Aliran Sungai Poso di Provinsi Sulawesi Tengah, Indonesia - Massiri, Sudirman Daeng; Hamzari, Hamzari; Pribadi, Hendra; Naharuddin, Naharuddin; Malik, Adam; Rauf, Abdul (Jurnal Ilmu Kehutanan, 2025)
Community-based collaborative watershed governance offers a potential solution to the limitations of government-led management by leveraging substantial social capital to sustain watershed functions. Therefore, this research aimed to investigate community social capital in watershed conservation and formulate strategies to strengthen it, promoting the sustainability of Poso Watershed. The investigation was conducted in Tentena and Sawidago Villages in Poso Watershed, using interviews with households and key informants, focus group discussions, and field observations. This research employed descriptive quantitative analysis to assess community social capital characteristics and levels, while applying SWOT (strengths, weaknesses, opportunities, and threats) analysis to develop strategies for strengthening social capital. The results showed that high cognitive-social capital required substantial structural social capital to generate collective action in watershed conservation. Weak structural social capital was reflected in the community’s limited understanding of formal rules and low involvement in organizations related to forest and watershed conservation, leading to weak solidarity and collective action. Strengthening social capital required harnessing the role of the Watershed Management Coordination Forum, which engages government and stakeholders in community-based collaborative watershed management. This primary strategy should be supported by improving communication, socialization, counselling, increasing community participation, and fostering the role of local institutions in watershed conservation.